USE OF AUTHENTIC VIDEO MATERIALS FOR THE FORMATION OF FUTURE ENGINEERS’ FOREIGN PROFESSIONAL COMMUNICATIVE COMPETENCE - Конопляник, Л. М.; Коваленко, О. О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article investigates the role of authentic video materials in learning a profession-oriented foreign language in higher educational institutions by future engineers. The authors reveal the special features of using video materials in classes, determine the benefits of using authentic video materials (creation of specific language environment, increase of motivation, attention and memory development, effective learning, etc) to improve students’ competences. The paper draws attention to the criteria of the selection of video materials (authenticity, compliance with the curriculum and topics, taking into account the interests of the target audience, information novelty and relevance, compliance with regulations of speech, compliance of language material with the foreign language level, length of video clips, image sharpness and sound quality) and describes the main stages of work with videomaterials in foreign language classes